Evaluation of renal blood flow using doppler sonography in children with acute-falciparum malaria in south-western Nigeria (2015)
Background: Renal blood flow evaluation during malaria illness is rarely done despite the high incidence of kidney injury from malaria and availability of doppler ultrasound scanners in malaria endemic areas. Aims: This study is to evaluate the renal blood flow changes using doppler ultrasonography among uncomplicated and complicated malaria subsets of pediatric patient with laboratory evidence of malaria parasitemia and without background clinical and laboratory evidence of renal impairment. And to compare these with parameter of age matched healthy pediatric control. Study Design: This was a prospective case control study of renal doppler indicies in children with acute malaria. Place of study: The study was conducted among pediatric patients presenting at the children outpatient clinics, emergency and pediatric wards of the University College Hospital(UCH), Ibadan Nigeria. Methodology: Doppler indicies of 602 kidneys were evaluated among 85 uncomplicated (UM), 85 complicated malaria (CM) children that presented within 24 hours and follow up scans on days 3 and 5 of thier illness. These were compared with that of 131 healthy children (control). Results: The main renal artery diameter of the CM group was 0.41+ 0.07mm, UM=0.48+0.09mm and 0.53+ 0.11mm (p=<0.001) in the control group. The main renal vein diameter were0.59+0.11mm and 0.48+0.10mm and 0.63+0.15mm (P=<0.000) among the CM, UM and the control group respectively. The PSV and EDV were slightly lower in the malaria groups than in the control group. PSV=49.01+18.21 cm/s in the UM and CM=50.71+19.68 cm/s. The control group PSV was 56.95 + 15.47 cm/s. AT was however significantly lower in the two malaria subgroups than in the control. (UM=47.70+18.28 cm/s CM=52.33+21.06 cm/s and control=75.20+27.66 cm/s respectively (p=< 0.000). The intrarenal S/D in UM was 2.73+ 0.49 and the CM group S/D was 3.05+ 0.65 and control =2.62+ 0.47 (P=0.04). Slightly lower but statistically insignificant mean values were seen in the RI and PI. Conclusion: The main renal arterial and vein diameters ans the intra renal vessel AT are significantly reduced during acute falciparum malaria illness. The intra-renal PSV and EDV are likely to be lower in acute falciparum malaria than in the normal healthy children. The intra-renal S/D are significantly higher in the UM and CM. Also, the PI and RI are likely to be higher in the malaria groups. The AT and S/D both showed inverse and direct relationship respectively as malaria severity worsens. We propose that renal doppler ultrasound can be used to monitor renal status and should be included in the management of children with acute malaria infection more so in malaria endemic area.